2022
DOI: 10.1021/acs.jpcc.2c05214
|View full text |Cite
|
Sign up to set email alerts
|

Non-Negligible Role of Multifunctional MXene Hosts for Li–S Batteries: Anchoring and Electrocatalysis

Abstract: Lithium−sulfur (Li−S) batteries have attracted great enthusiasm in recent years. Nevertheless, the serious shuttle effect of lithium polysulfides (Li 2 S n ), poor conductivity of S and intermediate products, and relatively slow dynamics make its commercial application face severe challenges. Here, functionalized M 2 CT 2 MXenes (M = Ti, Nb, Cr; T = bare, O, F, OH) were used as the sulfur host to build multifunctional cathodes, in which the inhibition of the shuttle effect by the anchoring effect and accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 53 publications
(95 reference statements)
1
17
0
Order By: Relevance
“…It is worth noting that the O groups of Ti 2 CO 2 /Nb 2 CO 2 are located on the M2 site, while the O groups of Cr 2 CO 2 prefer to locate on the C site, as previously reported in our work. 15 Zn-M 2 CO 2 was constructed on the pristine MXenes models (Fig. 2a).…”
Section: Computational Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the O groups of Ti 2 CO 2 /Nb 2 CO 2 are located on the M2 site, while the O groups of Cr 2 CO 2 prefer to locate on the C site, as previously reported in our work. 15 Zn-M 2 CO 2 was constructed on the pristine MXenes models (Fig. 2a).…”
Section: Computational Methodologymentioning
confidence: 99%
“…The metal atom orbitals (Ti-3d, Cr-3d, and Nb-4d) contribute the majority of their metallicity. In the case 15 where MXenes with a smaller lattice constant always have a stronger anchoring ability. Besides this, a wider DOS around the E Fermi level always leads to an increase in the energy levels of the valence band, which is beneficial for the excitation of electrons in MXene.…”
Section: Computational Methodologymentioning
confidence: 99%
“…24 Superconductivity was rst observed in Nb 2 CT x terminated with S, Se, or NH groups, while no superconducting transition was found for bare and O-terminated Nb 2 C. 16 Some M 2 CT 2 (T = O, OH or S)-based multifunctional sulfur cathodes were found to effectively suppress the shuttling effect and exhibit excellent cycle performance and high specic capacity in lithium-sulfur batteries. [25][26][27] Zhu et al showed the O, OH and F groups on Zr 2 CT x can be seemingly exchanged with S groups through the proposed reaction in CS 2 solution. 28 A number of Sfunctionalized MXenes have been reported as electrode materials for potential metal ion batteries due to their lower diffusion barrier and higher storage capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Their adsorption capacities are not satisfactory with the capacity less than 7 mg/L 10 . Polymeric resin have been well‐developed for wide application for water purification, metal ion adsorption and medical waste treatment, and so forth 11–17 . Although the crown ethers have been recognized as excellent binding units for alkali metal ion, its toxicity and high costs prevent direct modification on the polymeric resin to enhance the adsorption performance 18–27 .…”
Section: Introductionmentioning
confidence: 99%